ECONOMIC MODELING OF CORE INDICATORS THAT FORM UNIVERSITY HUMAN RESOURCES (ILLUSTRATED BY THE EXAMPLE OF OGAREV MORDOVIA STATE UNIVERSITY) - Yuriy V. Sazhin; Dmitriy N. Krymzin (Статистика и экономика, 2016)
Selection of core indicators that form the human resources of Ogarev Mordovia State University is implemented on the basis of application of multidimensional statistical methods. The quantitative relationships between these indicators and the factors influencing them by constructing regression equations for principal components are identified.